Nietzscheforschung (De Gruyter (A), 1994)
The yearbook offer a discussion forum for international scholarship on Nietzsche. Published since 1994 on behalf of the Nietzsche Society, it addresses issues in philosophy, culture, art history, religious theory, sociology, and political history that relate to Friedrich Nietzsche's thought and its reception. Each volume focuses on a particular theme, and includes biographical and source-related materials, images, and reviews.